Vendors' handling practices of edible long-horned grasshoppers (Ruspolia differens) products and implications on microbial safety - Mugo-Kamiri, Loretta; Imungi, Jasper K.; Njue, Lucy; Diiro, Gracious; Ombura, Fidelis Levi O.; Akutse, Komivi S.; Chrysantus, Tanga M.; Khamis, Fathiya M.; Subramanian, Sevgan (Frontiers in Microbiology, 2024)
Edible grasshopper, Ruspolia ruspolia, has nutritional and cherished cultural and economic importance to people from diverse cultures, particularly in over 20 African countries. It is consumed at home or commercially traded as sautéed, deep-fried, or boiled products. However, there is limited information on the hygiene practices of the vendors and the implications on the microbial safety of the final product. This research aimed at assessing the food safety knowledge, handling practices and shelf life of edible long-horned grasshopper products among vendors and the microbial safety of ready-to-eat products sold in 12 different markets in Uganda. Samples of raw, deep-fried and boiled grasshoppers were randomly collected from 74 vendors (62% street and 38% market vendors) and subjected to microbial analysis. Over 85% of the vendors surveyed had no public health food handler's certificate and >95% had limited post-harvest handling knowledge. Total aerobic bacteria (7.30–10.49 Log10 cfu/g), Enterobacteriaceae (5.53–8.56 Log10 cfu/g), yeasts and molds (4.96–6.01 Log10 cfu/g) total counts were significantly high and above the acceptable Codex Alimentarius Commission and Food Safety Authority of Ireland (FSAI) limits for ready-to-eat food products. Eight key pathogenic bacteria responsible for foodborne diseases were detected and these isolates were characterized as Bacillus cereus, Hafnia alvei, Serratia marcescens, Staphylococcus aureus, S. xylosus, S. scuiri, S. haemolyticus, and Pseudomonas aeruginosa. Findings from this study highlight the urgent need to create local and national food safety policies for the edible grasshopper “nsenene” subsector to regulate and guide street and market vending along the value chain, to prevent the transmission of foodborne diseases to consumers.